Analisis Kualitas Sumber Daya Manusia, Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Kantor Kecamatan Jombang Dimasa Pandemi - M. Yasak Yahdillah; Edy Swasono (Universitas Islam Kadiri, 2022)
This study aims to analyze whether simultaneusly, there is an influence of Quality of human resources, Work discipline, Work motivation on the performance of the Jombang sub-district office employees during the pandemic era. This study used is quantitative approach by using survey method. The respondents are 30 employee The data analysis method used is Multiple Linear Regression. The results revealed that (1) Simultanrusly, Quality of human resource, discipline, and motivation have a positive and significant effect on employee performance in Jombang sub-district, (2) Partially, Quality of human resource has a positive and significant effect on employee performance in Jombang sub-district, (3) Discipline has a positive and significant effect on employee performance in Jombang sub-district, and (4) Motivation has a positive and significant effect on employee performance in Jombang sub-district . It is recommended tbat the head of Jombang sub-district office should the maintain their performance and its ianfluence factors.